2009
DOI: 10.1136/adc.2008.139865
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal infections in Asia

Abstract: The incidence of late-onset sepsis was higher in Asia than in resource-rich countries, but the organisms isolated and mortality were similar. Over half of all Gram-negative bacilli were antibiotic resistant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
58
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 15 publications
15
58
2
1
Order By: Relevance
“…Al-Zwaini et al 61 Tiskumara et al 62 El-Said et al 63 Ben Hamida et al 64 Subtotal (I 2 =65·6%, p=0·033)…”
Section: Eastern Mediterraneanmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Zwaini et al 61 Tiskumara et al 62 El-Said et al 63 Ben Hamida et al 64 Subtotal (I 2 =65·6%, p=0·033)…”
Section: Eastern Mediterraneanmentioning
confidence: 99%
“…Western Pacific Angstetra et al 65 Daley et al 66 May et al 67 Tiskumara et al 62 Tiskumara et al 62 Kim et al 68 Niduvaje et al 69 Subtotal (I 2 =54·7%, p=0·039)…”
Section: Eastern Mediterraneanmentioning
confidence: 99%
“…Specimens from infants in the first 24 hours of life are also seriously under-represented, especially those from low birth-weight babies and babies born outside health facilities. 3,17,18 Intrapartum antibiotic prophylaxis against S. agalactiae has also led to a substantial change in the bacteria responsible for early onset neonatal sepsis; gramnegative bacilli and Staphylococcus spp. predominate in countries implementing these programs.…”
Section: -10mentioning
confidence: 99%
“…Rates and causative pathogens of neonatal sepsis can vary within the same unit, among units, and across countries [11,12,16,17]. The rates of sepsis in this study are comparable to those in units in Taiwan that reported rates ranging from 3% to 4% [18,19], but lower compared with data from other countries such as the Philippines, The Netherlands, and Nigeria, where sepsis rates have been reported to range from 15.1% to 19.6% [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, the overall cumulative incidence of EOS is from 0.8 to 1.0 cases per 1,000 live births [9] and the rate of LOS is 36% in preterm infants (22)(23)(24)(25)(26)(27)(28) weeks gestational age/401-1500 g birth weight) [10]. Similarly, two studies of groups of neonatal intensive care unit (NICUs) in developing countries including Malaysia, Thailand, China, and India, found the rate of EOS to be from 0.62 to 0.72 cases per 1,000 live births [11,12]. However, these studies also found a rate of LOS ranging from 2.0 per 1,000 live births in Hong Kong to 22.0 per 1,000 live births in Thailand [11].…”
Section: Brief Communication (Original)mentioning
confidence: 99%